Pemikiran Pendidikan Islam - Wulandari, Ayu; Sri Jumini (PT PUBLIKASI INSPIRASI INDONESIA, 2024)
Education has such an importantrole in human life, because the essence of education itself is to humanize and mature humans, so that they become fully human. Education is a process of guiding humans to become fully human and naturally as human beings who are the creation of Allah SWT. In education, the main thing that must be prepared is to formulate goals. With this aim, the educational process will be directed and carried out in a systematic and organized manner so as to produce education that meets expectations and does not deviate from the norms of life in society. The purpose of Islamic education cannot be separated from the purpose of human life as a servant of Allah, forming a Muslim person who truly believes in Allah and whose whole life is oriented to Allah alone. The aim of Islamic education in essence is to make humans as servants who truly believe and fear Allah which is reflected in their personality who has noble character, both in living in society and towards the environment or the universe. Thus, the purpose of Islamic education is based on the purpose of human life in this world as a Muslim. In the Koran, humans have at least three goals in life, namely to worship, to become caliphs and to know each other, in the sense of achieving a harmonious life in society. In the context of his relationship with his Lord, humans are servants of Allah who have the obligation to fulfill His servitude and devotion. Whereas in the context of relations with the universe he is the caliph, as the regulator and guardian of the universe. And to create a peaceful and prosperous universe, it is necessary to have shared responsibility in creating a peaceful world order. To make humans as pious servants, it needs a process through education. Thus, Islamic education is a tool to realize the purpose of human life in this world. Because without education, humans will not be able to become educated human beings so as to achieve the degree of pious